2005
DOI: 10.1073/pnas.0406993102
|View full text |Cite
|
Sign up to set email alerts
|

Neutral microepidemic evolution of bacterial pathogens

Abstract: Understanding bacterial population genetics is vital for interpreting the response of bacterial populations to selection pressures such as antibiotic treatment or vaccines targeted at only a subset of strains. The evolution of transmissible bacteria occurs by mutation and localized recombination and is influenced by epidemiological as well as molecular processes. We demonstrate that the observed population genetic structure of three important human pathogens, Streptococcus pneumoniae, Neisseria meningitidis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
139
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 23 publications
9
139
3
Order By: Relevance
“…This hypothesis, which is already debatable when semi/epidemic clonality is concerned, can hardly account for PCE features, in particular the presence of deep phylogenies (12). It should be noted that in the case of N. meningitidis the classical panselectionist hypothesis has been challenged by several authors (12,35,40).…”
Section: Is the Population Structure Of N Meningitidis Better Explaimentioning
confidence: 97%
“…This hypothesis, which is already debatable when semi/epidemic clonality is concerned, can hardly account for PCE features, in particular the presence of deep phylogenies (12). It should be noted that in the case of N. meningitidis the classical panselectionist hypothesis has been challenged by several authors (12,35,40).…”
Section: Is the Population Structure Of N Meningitidis Better Explaimentioning
confidence: 97%
“…The three published estimates of r/u are more consistent, each including 1. These are our estimate (0.7-1.2), the estimate of Jolley et al (2005) (0.16-1.8), and that of Fraser et al (2005) based on the distribution of allele sharing within a population (1.1). For Bacillus, 95% credibility regions for r/m and r/u based on our method are 1.3-2.8 and 0.2-0.5, respectively, showing that recombination is rare compared to the level observed in Neisseria or in many other bacteria.…”
Section: Applications To Datamentioning
confidence: 99%
“…A coalescent prior has the advantage of tractability and simplicity. However, it has been shown that for many bacterial populations, there is an excess of isolates with identical allelic profiles, in comparison to neutral expectations (Fraser et al 2005;Jolley et al 2005). Since bacteria do not disperse at each replication, different growth conditions in different physical locations could introduce local correlations in the genealogy.…”
mentioning
confidence: 99%
“…A wide spectrum of methods exist to estimate this ratio, using either microevolutionary techniques (Falush et al, 2001;Feil et al, 2004) or population genetics methodology (Fearnhead et al, 2005;Fraser et al, 2005;Jolley et al, 2005). The ratio r/y is a measure of the frequency at which recombination occurs relative to mutation and therefore has an intuitive interpretation: if for example r/y ¼ 2, recombination events occur two times as often as point mutation in the evolution of the population.…”
Section: Methodsmentioning
confidence: 99%